Komunikasi oroantral: etiologi dan penatalaksanaannya Oroantral communication: the etiology and management - Wiwiek Poedjiastoeti (DiscoverSys Inc., 2011)
Oroantral communication (OAC)may occur when upper posterior teeth are removed, and occasionally, as a resultof trauma. This sinus perforation formed particularly when a maxillary molar with widely divergent roots adjacentto edentulous spaces is extracted. In this instance the sinus is likely to be pneumatized into the edentulous alveolarprocessus surrounding the tooth, which weakens the entire alveolus and brings the tooth apices into a closerrelationship with the sinus cavity. In order to avoid OAC, preoperative radiograph is needed. When perforation, ifsinus opening is small and disease free, effort should be made to establish blood clot in the extraction site andpreserve it in place. Soft tissue flap elevation is not required. Sutures are placed to reposition the soft tissue, and agauze pack is placed over the surgical site for 1-2 hours. Majority of patients treated in this manner showeduneventful healing when no evidence of preexisting sinus disease.